Pelatihan Pemanfaatan Minyak Jelantah Menjadi Lilin Aromaterapi - Asfitri Hayati; Rella Dwi Respati; Raden Asri Kartini; Bagus Arstiyanto Prasetyo (Kolaborasi : Jurnal Hasil Kegiatan Kolaborasi Pengabdian Masyarakat, 2024)
This training aims to provide knowledge and skills to participants in processing used cooking oil into aromatherapy candles, as an effort to utilize household waste that is economically valuable and environmentally friendly. Used cooking oil, which is generally thrown away and can pollute the environment, can be processed into aromatherapy candles which have added value. This training includes material on basic techniques for processing used cooking oil, selecting aromatherapy ingredients, and the process of making candles until the product is ready for use. With this training, it is hoped that participants will be able to utilize used cooking oil waste creatively and productively, as well as opening up new business opportunities in the field of environmentally friendly products. The results of the training show that participants can easily understand and apply the knowledge provided, and produce quality aromatherapy candles that are ready to be marketed.